Female sexual dysfunction in patients with urinary incontinence and lower urinary tract symptoms - Raheela Mohsin; Wajahat Aziz (Journal of the Pakistan Medical Association, 2022)
This study was conducted to determine the frequency of female sexual dysfunction in patients with urinary incontinence and lower urinary tract symptoms (UI/LUTS). Female patients between 18 and 60 years of age with lower urinary tract symptoms for more than three months were included and Female Sexual Function Index (FSFI) questionnaire was administered. Ninety-seven patients with mean age of 48+/-12.61 years were included in this cross sectional study. Median FSFI score of our patients was 46 (IQR34-58). Moderate to severe effect of urinary symptoms on sexual life was reported by 71 (73%) patients. When patients with sexual dysfunction (FSFI<27) were compared with those without sexual dysfunction (FSFI>27) there was no difference in age, parity, menopausal status or severity of LUTS between the two groups. We conclude that sexual dysfunction is common among female patients presenting with LUTS irrespective of age, menopausal status or severity of LUTS. Keywords: Lower Urinary Tract Symptoms, Urinary Incontinence, Female Sexual Dysfunction